Analysis of Facilities and Infrastructure Management, Teacher Activeness in MGMP, and Professional Competence of Physical Education Teachers on Teacher Performance in Public High Schools in Rembang Regency - PUGUH CAHYO WAHONO; Setyawati, heny; Rahardjo, Hermawan Pamot (Universitas Negeri Semarang, 2024)
This study aims to analyze the influence of infrastructure management, teacher participation in the Subject Teacher Consultation (MGMP), and the professional competence of Physical Education teachers on teacher performance. The method used in this research is a survey with a quantitative approach. Data were collected from 30 Physical Education teachers in nine state senior high schools in Rembang Regency. The results of the study show that good infrastructure management and active participation of teachers in MGMP forum positively contribute to the improvement of professional competence and teacher performance. Specifically, adequate infrastructure allows Physical Education teachers to perform their duties more effectively, while active participation in MGMP forum provides opportunities for teachers to share experiences, increase knowledge, and develop their professional skills. It was also found that the integration of these three factors can enhance teaching effectiveness and student motivation, as well as contribute to higher academic achievement. This research has significant implications for education management, particularly in improving the quality of Physical Education teaching through the optimization of infrastructure and increased active participation in MGMP forum. The findings indicate that schools and local governments need to pay more attention to providing adequate facilities and supporting active teacher participation in MGMP forum. Additionally, enhancing teacher professional competence through continuous training and professional development should be prioritized to achieve better educational quality in Indonesia. Furthermore, the results of this study can serve as a basis for the development of policies and training programs aimed at improving teacher performance, which will ultimately have a positive impact on overall educational quality.